Integrative Model of Tourism-Education Synergy for Sustainable Rural Development: A Systematic Literature Review - Yohanis Tarukallo (Journal of Innovative and Creativity, 2025)
This study aims to analyze the contribution of tourism to educational development within the context of sustainable development by reviewing and synthesizing previous research through a Systematic Literature Review (SLR) approach. Twenty selected articles published between 2020 and 2025 were analyzed using the PRISMA framework. Data were collected through a systematic selection process based on inclusion criteria focusing on tourism, education, and sustainable rural development. The analysis reveals that tourism contributes to education through three main mechanisms: culture- and society-based education, sustainable environmental education, and economic education through local entrepreneurship. The key determinants of successful integration between tourism and education include community participation, policy support, cultural values, educational capacity, and economic sustainability. This research proposes a conceptual model, the Tourism–Education Synergy, which explains the reciprocal interaction between tourism activities and community learning processes as the foundation of sustainable development. The findings affirm that tourism is not merely an economic sector but also a social learning system that enhances human capacity at the local level.